2020
DOI: 10.5194/angeo-2020-60
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the Electrodynamic Method to Derive Height-Integrated Ionospheric Conductances

Abstract: Abstract. We have used empirical models for electric potentials and the magnetic fields in both space and on the ground to obtain maps of the height-integrated Pedersen and Hall ionospheric conductivities at high latitudes. This calculation required use of both "curl-free" and "divergence-free" components of the ionospheric currents, with the former obtained from magnetic fields that are used in a model of the field-aligned currents. The second component is from the equivalent current, usually associated with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 45 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…(10). This model version (Edwards et al, 2020) had fit the spacecraft magnetic field measurements to the duskward and sunward components in order to reduce the spurious, circular harmonics in the FAC that tend to result when using polar coordinates. The total sums of the upward (negative) and downward (positive) FAC, integrated over the spherical cap, are indicated in the upper left and right corners of the contour map in units of millions of amperes (MA).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(10). This model version (Edwards et al, 2020) had fit the spacecraft magnetic field measurements to the duskward and sunward components in order to reduce the spurious, circular harmonics in the FAC that tend to result when using polar coordinates. The total sums of the upward (negative) and downward (positive) FAC, integrated over the spherical cap, are indicated in the upper left and right corners of the contour map in units of millions of amperes (MA).…”
Section: Resultsmentioning
confidence: 99%
“…The field-aligned current maps obtained from different data sets are also similar and repeatable. For examples, compare the results from magnetometers on Dynamics Explorer 2 (Weimer, 2001(Weimer, , 2005a, DMSP , the Iridium constellation (Anderson et al, 2008), CHAMP and Swarm (Laundal et al, 2018), and the Ørsted-CHAMP-Swarm combination (Edwards et al, 2020) that we use here. Laundal et al (2018) also show maps of the equivalent currents that resemble the ones shown here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations